2012
DOI: 10.1002/cbdv.201100336
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Transformation and Schistosomicidal Effects of Pimaradienoic Acid

Abstract: The schistosomicidal effects of pimaradienoic acid (PA) and two derivatives, obtained by fungal transformation in the presence of Aspergillus ochraceus, were investigated. PA was the only compound with antischistosomal activity among the three diterpenes studied, with the ability to significantly reduce the viability of the parasites at concentrations ranging from 25 to 100 μM. PA also promoted morphological alterations of the tegument of Schistosoma mansoni, separated all the worm couples, and affected the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In the latter case, the parasiticidal effect of the organism was thought to be exerted through protein metabolism. Pimaradienoic acid and two derivatives from Aspergillus ochraceus exhibited promising anti‐ S. mansoni activity at 25 to 100 μM (Porto et al ., ). A similar activity was also observed when S. mansoni was treated with phytol in 50 to 100 µg/mL (de Moraes et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In the latter case, the parasiticidal effect of the organism was thought to be exerted through protein metabolism. Pimaradienoic acid and two derivatives from Aspergillus ochraceus exhibited promising anti‐ S. mansoni activity at 25 to 100 μM (Porto et al ., ). A similar activity was also observed when S. mansoni was treated with phytol in 50 to 100 µg/mL (de Moraes et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…An in vitro study with pimaradienoic acid ( 6 ), a major diterpene isolated from Viguiera arenaria , promoted morphological alterations of the S. mansoni tegument and caused the separation of 100% of the coupled adult worms into individual male and female worms at a concentration of 100 µM after 24 h of exposure, thus justifying the absence of egg production at this concentration [ 66 ]. A preliminary in vivo study with experimentally infected mice also indicated that, at a dose of 100 mg/kg/day, compound 6 reduced the total number of adult S. mansoni worms by about 40%.…”
Section: Natural Products As Lead Compounds Against Schistosomiasimentioning
confidence: 99%
“…A preliminary in vivo study with experimentally infected mice also indicated that, at a dose of 100 mg/kg/day, compound 6 reduced the total number of adult S. mansoni worms by about 40%. Moreover, compound 6 was devoid of in vitro cytotoxicity against a human fibroblast cell line at a broad concentration range (7.8–500 µM), indicating its selectivity [ 66 ].…”
Section: Natural Products As Lead Compounds Against Schistosomiasimentioning
confidence: 99%
“…mansoni worms. [ ][ ][ ] Here, we observed that the active compounds significantly affected both female and male worms.…”
Section: Resultsmentioning
confidence: 89%